Unilateral Blaschkoid lichen planus in successive pregnancies - Shiva Kumar; Rajendra Okade; Yasmin Abdul Rahman (PAGEPress Publications, 2011)
A  number  of  genetic, congenital  and  acquired dermatoses  have  been  known  to  follow  Blaschko's lines. A  common  disorder  like  lichen  planus  can very  rarely  present  with   pruritic  lesions  in  atypical  patterns  such  as  unilateral  distribution,  painful  eruptions  and  along  Blaschko's  lines. Various  triggering  factors  varying  from  viral infections  and  vaccinations   to  trauma  have  been  implicated in lichen  planus.  We  describe  a  female  patient  in  the second  trimester  of  her  second  pregnancy  who  developed  unilateral  lichen  planus  along  Blaschko's  lines  during  both  pregnancies.  No  case  of  lichen planus  along  Blaschko's  lines  recurring  during  pregnancy  is reported  so far. Could  pregnancy  itself  be  a  contributory  factor   towards  onset  of  lichen  planus  in  this  case?